Answer: D. -2(-4.5m + 4n)
Explanation:
First, let us simplify -1.5(-6m+8n).
Given:
-1.5(-6m + 8n)
Distribute:
9m - 12n
[A] ✗
9 /3 = 3 and 12 / 3 = 4
This means that 3(3m - 4n) = 9m - 12n = -1.5(-6m+8n)
Option A is not our answer.
[B] ✗
Using this simplified version we did above, option B is not our answer as 9m - 12n = 9m - 12n and 9m - 12n = -1.5(-6m+8n).
[C] ✗
We will distribute option C to see if we reach the same expression. Seeing below, we do, so option C is not our answer.
-6(-1.5m + 2n)
9m - 12n
[D] ✓
Since none of the other options are correct, the answer to your question D because it is not equivalent.
Answer:
D. -2(-4.5m + 4n)